The Kingdom of Kongo and the Counter Reformation - Thornton, John K. (Social sciences and missions, 2013)
From early contact with the Portuguese and conversion to Christianity in the late 15th century and continuing through the Counter Reformation, the Kingdom of Kongo resisted Portuguese colonialism while remaining steadfastly loyal to the Roman Catholic Church. Against the turbulent backdrop of the growing Atlantic slave trade, internal conflict and power struggles, and Portuguese presence in Luanda, Kongo repeatedly resisted the temptation to break from Rome and establish its own Church, in spite of Portuguese control of the Episcopate. In the late 16th century King Álvaro clashed with the Portuguese Bishop, but remained faithful to the church in Rome. In the early 17th century, Kongo armies repelled Portuguese invasions from the south while kings continued to lobby for more Jesuit and later Italian Capuchin missionaries, whom they needed, above all, to perform sacraments vital to Kongolese Catholics. Another opportunity to split from Rome came when Dona Beatriz Kimpa Vita created the Antonian movement in 1704 and denounced the Catholic Church. Instead, she was captured and burned at the stake while King Pedro IV remained faithful to the Capuchin missionaries. In contrast to Portuguese Angola, where Jesuits were deeply implicated in slave trading, the Capuchins in Kongo did not own slaves and, for the most part, both resisted and criticized the slave trade.